A Study of Buton Society Local Wisdom in Conserving The Gender Based Forest - Husain, Najib (Advances in Social Sciences Research Journal, 2017)
The purpose of this study is to find out how Buton society in conserving the gender based forest using local wisdom approach. In Southeast Sulawesi specifically in Buton Regency has a certain area of reserved forest called Kaombo whose existence is closely related to the public interest led by a local actor called Parabela. One of them is located in Takimpo Urban Village, Pasarwajo Sub-district of Buton Regency. Inside the Kaombo area located in the area is divided into 6 preserved Kaombo Locations. One of them is Kaombo Ohusii (Widow Forest). Kaombo Ohusii (Widow Forest) is a future forest as a historical heritage in the era of Buton sultanate. Since the reign era of Buton Sultanate IV Dayanu Ikhsanuddin (1578-1615), people who can take the proceeds from the widow forest are only those who are widowed or elderly women. It proves that since ancient times, Buton tribe has been familiar with gender concepts and gender sensitive. This study was conducted in Takimpo Urban Village, Pasar Wajo Sub-district of Buton Regency. The selection of location is based on consideration which in this area is a gender based forest using traditional wisdom management. The type of this study was descriptive qualitative. The researcher determined the informant intentionally (purposive) consisting of the key informant called Former Parabela (Kayaro) who know the condition in this area, the informant is Parabela and custom people and woman with the total was 8 people in Takimpo urban village. There were two data collection techniques which researchers used in this study, namely in-depth interviews and through direct observation in the location of the study. To analyze the data have been obtained, then the data obtained would be grouped by types of problems. Data analysis was conducted since the beginning of the study until the end of the whole study process. The result of the study showed that the local wisdom of Buton society in conserving the gender based forest is Kaombo Ohusii, managed directly by customary institution under Parabela's leadership and its equipment, even though all of them are men but they are very concerned about women's interests. The function of customary institutions in the management of Kaombo Ohusii is as a supervising and guardian for each activity undertaken by the society. Customary institutions also aims as a controller of all actions taken related to the management of widow forest area. As time of the development nowadays, after the migration of the custom people of Takimpo Lipuogena who had settled in the mountains then moved to the coast, the function of the Ohusii Kaombo area, which was felt greatly the benefit by the widows and poor women, turned into a lack of attention. Keywords: local wisdom, and conserving the gender based forest